Answer:
For the function [tex]$f(x)=4 x-3$[/tex] the average rate change from x is equal 1 to x is equal 2 is 4 .
Step-by-step explanation:
A function is given f(x)=4x-3.
It is required to find the average rate change of the function from x is 1 to x is 2 . simplify.
Step 1 of 2
A function f(x)=4 x-3 is given.
Determine the function [tex]$f\left(x_{1}\right)$[/tex] by putting the value of x=1 in the given function.
[tex]$\begin{aligned}&f(1)=4(1)-3 \\&f(1)=1\end{aligned}$$f(1)=1$[/tex]
Determine the function [tex]$f\left(x_{1}\right)$[/tex] by putting the value of x is 2 in the given function.
[tex]$\begin{aligned}&f(2)=4(2)-3 \\&f(2)=5\end{aligned}$[/tex]
Step 2 of 2
According to the formula of average rate change of the equation [tex]$\frac{\Delta y}{\Delta x}=\frac{f\left(x_{2}\right)-f\left(x_{2}\right)}{x_{2}-x_{1}}$[/tex]
Substitute the value of [tex]$f\left(x_{1}\right)$[/tex] with, [tex]$f\left(x_{1}\right)$[/tex] with [tex]$3, x_{2}$[/tex] with 2 and [tex]$x_{1}$[/tex] with 1 .
[tex]$\begin{aligned}&\frac{\Delta y}{\Delta x}=\frac{5-1}{1} \\&\frac{\Delta y}{\Delta x}=4\end{aligned}$[/tex]